Robust anticipative energy management system: Application of a smart building platform. (March 2017) - Le, Minh-Hoang; Ploix, Stephane
Robust energy management in buildings is addressed in this paper. The energetic impact of buildings in the current energetic context is first presented. Then the studied optimization problem is defined as the optimal management of production and consumption activities in buildings. A scheduling problem is identified to adjust the energy consumption to both the energy cost and the user's comfort. The available flexibility of the services provided by domestic appliances is used to compute optimal energy plans. These flexibilities are associated to time windows or heating storage abilities. A constraints formulation of the energy allocation problem is given. A derived mixed linear program is used to solve this problem. The energy consumption in houses is very dependent on uncertain data such as weather forecasts and inhabitants' activities. Parametric uncertainties are introduced in the home energy management problem in order to provide robust energy allocation. Robust linear programming is implemented. A scenario-based approach is implemented to face this robust optimization problem. Practical application : Because of the increasing part of renewable energy in electricity production, which is difficult to control, consumers will have to become more involved in the grid management. This paper states the problem of energy management in buildings and describes the optimization problem defined to adjust the energy consumption of buildings to production constraints. This decision system is based on the weather forecasts and a variable cost of electricity. Parametric uncertainties on the data are taken into account in order to propose robust energy planning in which a performance is guaranteed over the expected data.